GIS-material for the archaeological project: Settlement remains at Östra Eneby vicarage - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of a 3G base station, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed preliminary investigations within two areas partly covering the so-called Pryssgården settlement site, RAÄ 166, in Östra Eneby parish, Norrköping. In area 1, located within the RAÄ 166 site and nearby the demolished vicarage of Östra Eneby, settlement remains such as pits and post holes were found. No features or finds were discovered within area 2.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine the type and intensity of the archaeological remains and, if possible, to delimit and date the remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har utfört en arkeologisk förundersökning vid två områden inom och i anslutning till RAÄ 166, den s k Pryssgårdsboplatsen, Östra Eneby socken, Norrköping. Anledningen var en planerad basstation för en 3G-mast. Inom Omr 1, beläget inom RAÄ 166 och i anslutning till den numera rivna Östra Eneby prästgård, påträffades boplatslämningar i form av gropar och stolphål. Inom Omr 2 påträffades varken anläggningar eller fynd.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att klargöra art och intensitet av lämningar, samt att eventuellt begränsa fornlämningsområdet och om möjligt datera framtagna lämningar.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatslämningar vid Östra Eneby prästgård
Keywords: Early Iron Age; äldre järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi